2017
DOI: 10.1128/jvi.01729-16
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Isfahan Virus and Vesicular Stomatitis Virus Vaccine Vectors Provide Durable, Multivalent, Single-Dose Protection against Lethal Alphavirus Challenge

Abstract: The demonstrated clinical efficacy of a recombinant vesicular stomatitis virus (rVSV) vaccine vector has stimulated the investigation of additional serologically distinct Vesiculovirus vectors as therapeutic and/or prophylactic vaccine vectors to combat emerging viral diseases. Among these viral threats are the encephalitic alphaviruses Venezuelan equine encephalitis virus (VEEV) and Eastern equine encephalitis virus (EEEV), which have demonstrated potential for natural disease outbreaks, yet no licensed vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…The members of genus Vesiculovirus are mainly arthropod-borne viruses that are transmitted by biting insects, most likely sandflies (Nasar et al 2017 ). The Isfahan virus (ISFV) is the unique member in genus Vesiculovirus that has been isolated from Hy.…”
Section: Mononegaviralesmentioning
confidence: 99%
“…The members of genus Vesiculovirus are mainly arthropod-borne viruses that are transmitted by biting insects, most likely sandflies (Nasar et al 2017 ). The Isfahan virus (ISFV) is the unique member in genus Vesiculovirus that has been isolated from Hy.…”
Section: Mononegaviralesmentioning
confidence: 99%
“…Interference has been observed with other alphavirus vaccines (44-48). However, we recently showed that this phenomenon was not observed when blended EEEV and VEEV vaccines, based on the replication-competent Isfahan virus platform, were administered to mice (49). The difference in the induction of interference may reflect the inherent biological differences in different vaccine platforms or may increase with use of three or more components in the multivalent administration.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque assays. Titration of EILV chimeras was performed on ϳ80% confluent C7/10 cell monolayers seeded overnight in six-well plates as described here, while all other viruses were titrated on Vero cells as described previously (49). Duplicate wells were infected with 0.1-ml aliquots from serial 10-fold dilutions in 1ϫ DMEM supplemented with 2% penicillin-streptomycin, 0.4 ml of medium was added to each well to prevent cell desiccation, and virus was adsorbed for 1 h. Following incubation, the virus inoculum was removed and cell monolayers were overlaid with 3 ml of a 1:1 mixture of 2% tragacanth and 2ϫ minimal essential medium with 5% FBS, 2% tryptose phosphate broth solution, and 2% penicillin-streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…All arthropod cells were stored in a humidified incubator at 28 C in 5% CO 2 . The passage ranges of the cell cultures used during these experiments were as follows: Vero (passages 8-96), C6/36 (6)(7)(8)(9)(10)(11)(12), CuVa (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), LL-5 (94-100), 4a3b (91-121). All cell cultures tested negative for mycoplasma.…”
Section: Cell Linesmentioning
confidence: 99%
“…11 VSV has proven to be a successful vector in the development of several live-attenuated vaccine candidates due to its ability to accept and stably express foreign gene products from heterologous viruses. [20][21][22][23][24][25][26] To develop a safe and efficacious single-dose vaccine against ZEBOV, the G gene of VSV was replaced with the immunogenic glycoprotein (GP) gene of ZEBOV, resulting in VSV virion particles expressing ZEBOV GP as the surface antigen. [27][28][29][30] The resulting rVSVDG-ZEBOV-GP construct, also referred to as V920, is a replication competent, live-attenuated vaccine that has attenuated replication and a narrower host-cell tropism in vitro than wild-type VSV.…”
Section: Introductionmentioning
confidence: 99%